Chemical freeze-out parameters via a nonperturbative QCD approach - Lu, Yi; Chen, Muyang; Bai, Zhan; Gao, Fei; Liu, Yu-xin (Physical review, 2022)
By analyzing the calculated baryon number susceptibility ratios χB1/χB2 and χB3/χB1 in a two-flavor system via the Dyson-Schwinger equation approach of QCD, we determine the chemical freeze-out temperature and baryon chemical potential in cases of both thermodynamic limit and finite size. We calculate the center-of-mass energy dependence of the χB4/χB2(κσ2) at the freeze-out line and find an excellent agreement with experimental data when taking into account the finite size effect. Our calculations indicate that the κσ2 exhibits a nonmonotonic behavior in the lower collision energy region. We also predict that the collision energy dependence of χB6/χB2 is nonmonotonic.